(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
contributo sottoposto a valutazione SOMMARIO: 1. Profili problematici emersi in recente giurisprudenza amministrativa - 2. La difficile qualificazione dei contenuti dell’attività alternativa - 3. Un valore insito nel sistema: il pluralismo delle agenzie formative. ABSTRACT : Teaching about Roman Catholic religion is a well-known issue for Italian scholars. The aim of these brief thoughts and reflections is to underline how many aspects still seem unclear or even misunderstood, because theadministrative jurisprudence has not yet shown precise considerations and decisions about it and new Agreements between Church and State contain some interesting positions, but the accepted principles need to find a formally correct and rational discipline to be completely realised. Many juridical problems get deeper, when the attention is focused on other religious traditions and on the idea of providing alternative subjects. The main question still consists in defining this kind of alternatives and reaching a high level of pluralism, without forgetting the typical status of religious teachings in the Italian system. KEY-WORDS: Irc, Private and Public School, legal pluralism